Demonstration versus the use of flowchart a comparison of two methods in the acquisition of psychomotor skills in the operation of automated clinical instrument - Nidea, Maria Dinna T.
Motor learning skill is very important for a successful healthcare professional. The medical technologist as a laboratory diagnostician is crucial in making medical decisions for physicians. The purpose of this study is to determine the effectiveness of training utilizing demonstration as compared to training with the use of flowchart in the acquisition of psychomotor skills in processing clinical specimen using automated clinical chemistry analyzer. The study was done in one of the universities that offers Bachelor of Science in Medical Technology course and conducted the training on the operation of automated analyzer to third year medical technology students. This study utilized quasi-experimental research design with pretest and post test.Training utilizing demonstration on the operation of an automated clinical chemistry instrument was conducted to the experimental group while training utilizing flowchart was done to the control group. The two teaching methods were compared to determine the effectiveness in the acquisition of skills. The evaluation of students practical examination was done and showed that there was statistically significant difference between the two groups in the acquisition of psychomotor skills (p-value=0.0081). Although findings of this study showed that there was a statistical difference, it was evidently shown that the students in both demonstration and flowchart had learned most of the psychomotor skills. Revising and emphasizing on those critical steps in the flowchart where students failed most may help improve and make it as effective as demonstration.